PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK DI KELAS XI FASE F SMA NEGERI 7 PADANG - Hamida, Zalika (Jurnal Edukasi dan Penelitian Matematika, 2023)
Math, particularly for high school drivers, must prepare pupils to address real-world situations. Students' arithmetic skills are poor. In class X Phase E of SMA Negeri 7 Padang, the proportion of students who answered correctly question 8 of Daily Assessment II and mathematical problem-solving stages are evidence. These issues are addressed via Problem Based Learning (PBL). Quasi experimentation and Non-equivalent Posttest Only Control Group Design were utilised. Simple random sampling was used to get experimental class XI F2 and control class XI F1. The final test analysis using the t test yielded a P-value = 0.002, indicating that students who learn using the Problem Based Learning model can solve maths problems better than those who learn directly in class XI Phase F SMA Negeri 7 Padang.Keywords  – Mathematical Problem-Solving Abilities, Problem Based Learning, Direct Learning